The role of prolactin levels in metabolic syndrome: a systematic review - Karolina Korta; Anna Szeliga; Karolina Oluszczak; Agata Szostak; Liliana Dyląg; Konrad Wawszkowicz; Kinga Szopińska; Maria Janina Śmigielska-Mikołajczyk; Weronika Łowicka; Magdalena Graca (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Prolactin is primarily associated with lactation and gonadal function, but it also has metabolic effects. Recent research shows prolactin's role in food intake, body weight, glucose, and lipid profile. Both low and excessive prolactin levels can lead to metabolic dysfunctions such as metabolic syndrome, type 2 DM, and dyslipidemia. Dopamine agonists, like cabergoline, used to treat hyperprolactinemia, may help balance metabolic homeostasis, likely due to their effect on prolactin. This study aims to synthesize current research on prolactin's metabolic effects, focusing on metabolic syndrome. State of knowledge: Metabolic syndrome is a cluster of dysfunctions like central obesity, atherogenic dyslipidemia, hypertension, and insulin resistance. It increases the risk of diabetes and cardiovascular diseases, affecting a quarter of the European population. Different combinations of metabolic syndrome components require various treatment approaches. New research focuses on prolactin and dopamine agonists in its pathogenesis and treatment. Materials and methods: This literature review is based on PubMed materials using keywords "prolactin," "hyperprolactinemia," "hypoprolactinemia," "metabolic syndrome," "diabetes mellitus," "obesity." Conclusions: This study highlights prolactin's importance in metabolic homeostasis, finding a positive correlation between both low and high prolactin levels and metabolic syndrome. However, gender differences and the pathogenesis of metabolic disorders should be further explored.